A proof-of-principle pharmacokinetic, pharmacodynamic, and clinical study with purine nucleoside phosphorylase inhibitor immucillin-H (BCX-1777, forodesine) - Gandhi, Varsha (© 2005 by The American Society of Hematology, 2005)
The discovery of purine nucleoside phosphorylase (PNP) deficiency and T lymphocytopenia suggested that inhibition of this enzyme could serve as a therapeutic target. Inhibitors of PNP failed until structure-based synthesis of immucillin-H (BCX-1777, forodesine), a transition-state analog of PNP. The picomolar potency for PNP, T cell-selective cytotoxicity, and animal studies provided the rationale for use of forodesine in T-cell malignancies. Five patients were treated with an intravenous infusion of forodesine (40 mg/m(2)) on day 1; treatment continued on day 2; forodesine was administered every 12 hours for an additional 8 doses. Plasma and cellular pharmacokinetics and pharmaco-dynamics were investigated. Median peak level of forodesine (5.4 μM) was achieved at the end of infusion. This level was sufficient to increase plasma 2′-deoxyguanosine (dGuo) concentrations in all patients. Intracellular deoxyguanosine triphosphate (dGTP) increased by 2- to 40-fold in 4 of 5 patients (8 of 9 courses) and correlated with antileukemia activity in 4 patients. However, objective responses were not observed. This was the first clinical study in humans to demonstrate the plasma pharmacokinetics and the pharmacodynamic effectiveness of the PNP inhibitor, forodesine; however, regrowth of leukemia cells in the blood and marrow after course 1 suggested that a different therapeutic schedule should be considered for future studies.